An Integrated Systems Approach Unveils New Aspects of Microoxia-Mediated Regulation in Bradyrhizobium diazoefficiens - Fernández, Noemí; Cabrera, Juan J.; Varadarajan, Adithi R.; Lutz, Stefanie; Ledermann, Raphael; Roschitzki, Bernd; Eberl, Leo; Bedmar, Eulogio J.; Fischer, Hans-Martin; Pessi, Gabriella; Ahrens, Christian H.; Mesa, Socorro (Frontiers in Microbiology, 2019)
The adaptation of rhizobia from the free-living state in soil to the endosymbiotic state comprises several physiological changes in order to cope with the extremely low oxygen availability (microoxia) within nodules. To uncover cellular functions required for bacterial adaptation to microoxia directly at the protein level, we applied a systems biology approach on the key rhizobial model and soybean endosymbiont Bradyrhizobium diazoefficiens USDA 110 (formerly B. japonicum USDA 110). As a first step, the complete genome of B. diazoefficiens 110spc4, the model strain used in most prior functional genomics studies, was sequenced revealing a deletion of a ~202 kb fragment harboring 223 genes and several additional differences, compared to strain USDA 110. Importantly, the deletion strain showed no significantly different phenotype during symbiosis with several host plants, reinforcing the value of previous OMICS studies. We next performed shotgun proteomics and detected 2,900 and 2,826 proteins in oxically and microoxically grown cells, respectively, largely expanding our knowledge about the inventory of rhizobial proteins expressed in microoxia. A set of 62 proteins was significantly induced under microoxic conditions, including the two nitrogenase subunits NifDK, the nitrogenase reductase NifH, and several subunits of the high-affinity terminal cbb3 oxidase (FixNOQP) required for bacterial respiration inside nodules. Integration with the previously defined microoxia-induced transcriptome uncovered a set of 639 genes or proteins uniquely expressed in microoxia. Finally, besides providing proteogenomic evidence for novelties, we also identified proteins with a regulation similar to that of FixK2: transcript levels of these protein-coding genes were significantly induced, while the corresponding protein abundance remained unchanged or was down-regulated. This suggested that, apart from fixK2, additional B. diazoefficiens genes might be under microoxia-specific post-transcriptional control. This hypothesis was indeed confirmed for several targets (HemA, HemB and ClpA) by immunoblot analysis.